Macromarketing Vol.3 A global focus marketing systems, societal development, equity and poverty - Tadajewski, Mark (Ed); Shultz, Clifford J. (Ed); Shapiro, Stanley J.(Ed) (Los Angeles SAGE Publications, 2009)
Controversies in development1: benefits from freer trade